Réponses

  • Utilisateur Brainly
2014-09-09T16:44:57+02:00
A= - 3(a² + 2) - (a - 3)(2a + 7)
A= - 3a² - 6 - (2a² + 7a - 6a - 21)
A= - 3a² - 6 - 2a² - a + 21
A= - 5a² - a + 15

B= - 5(x + 5) + (3x - 1)(- 4x + 3) + 7x - 9
B= - 5x - 25 - 12x² + 9x + 4x - 3 + 7x - 9
B= - 12x² + 15x - 34

C= 2(7x² - 1) - (4 + x)(x - 6) - (x + 7)
C= 14x² - 2 - (4x - 24 + x² - 6x) - x - 7
C= 14x² - x - 9 - 4x + 24 - x² + 6x
C= 13x² + x + 15

D= 7 - 5(2x + 1) - (8 + 4x)2x + 8
D= 7 - 10x - 5 - 16x - 8x² + 8
D= - 8x² - 26x + 10